Development of algorithms for assessing risks and vulnerability to anthropogenic impacts - Kuznetsova Inna; Chistyakov Alexander; Porksheyan Marcos (E3S Web of Conferences, 2022)
The paper presents currently used approaches to the assessment of water pollution by various types of pollutants. Based on the existing criteria, an algorithm for assessing risks and vulnerability to anthropogenic impacts is proposed. The software package obtained on their basis makes it possible to model the processes of the spread of pollutants in the studied water area, to detect and evaluate the power of sources of pollutants and manage them, to assess risks and vulnerabilities in relation to anthropogenic impacts, to carry out zoning of the water area of a shallow water body in accordance with the levels of anthropogenic loads, to carry out environmental design from the standpoint of sustainable development.